Exploring the Meaning of Ramadan from the Perspectives of Islam in America and Indonesia: A Corpus-Based Analysis - Sasnitya, Raden; Kurniawan, Eri; Supriadi, Rinaldi; Qodri, Asri Nurul (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The diverse cultural interpretations and expressions of Ramadan across different societies have not been extensively examined through a linguistic perspective, especially comparing Muslim-majority and minority contexts. This study aims to investigate how the word